Walking the Talk: LGBTQ Allies in Australian Secondary Schools - Vicars, Mark; Van Toledo, Samara (Frontiers in Sociology, 2021)
Sexual culture(s) are an active presence in the shaping of school relations, and LGBTQ issues have long been recognized as a dangerous form of knowledge in school settings. Queer issues in educational domains quickly attract surveillance and have historically often been aggressively prosecuted and silence enforced. This paper examines the intersections of straight allies in promoting an LGBTQ visibility and agency in Australian secondary schools. Drawing on interviews with “straight”-identified secondary students, a narrative methodology was utilized to explore the presence of student allies for making safe schools. Drawing on straight secondary students' responses to LGBTQ issues in their schools, firsthand accounts of intervening in heteronorming school cultures focus on experiences of being an ally to address LGBTQ inclusivity in Australian secondary schools.